The effect of ASEAN-korea free trade agreement (AKFTA) on Indonesia trade: a gravity model approach - Arjun Saka Agung; Zulkarnain Ishak; Imam Asngari; Abdul Bashir (Jurnal Ekonomi Pembangunan, 2019)
The aim of this research is to analyze the effect of ASEAN Korea Free Trade Agreement (AKFTA) on Indonesia Trade with gravity model approach using panel data. This research is using Hausman and Chow test to choose the best between the Fixed Effect model (FEM) and Random Effect Model (REM). The test result shows that REM is the best model choosen to analyze the effect from GDP per capita, Exchange rate, distance and AKFTA Policy to the import from 14 AKFTA country economies to Indonesia. The result from R2 shows that the variation of independent variables (GDP per capita, Exchange rate, distance and AKFTA Policies) affected the variation of dependent variable (Import) as 54 percent. Meanwhile, from the gravity theory, the trade among AKFTA economies to Indonesia has bring positive impact as the distance has positive sign and lead to form trade creation. The variable of dummy policy has negative and significantly affected the import.